Daya Dukung Biofisik Sub Daerah Aliran Sungai Ciujung Hulu, Provinsi Banten: Biophysical Carrying Capacity of the Upper Ciujung Sub Watershed in Banten Province - Naitkakin, Egidius; Rachman, Latief Mahir; Hidayat, Yayat (Universitas Hasanuddin, 2023)
Landuse changes without soil and water conservation-based, especially in the upstream watershed, can drive erosion and degraded land. It affects watershed management. Flood, sedimentation, and discharge fluctuation downstream of Ciujung Watershed are the effect of the degraded land upstream. It affects biophysical carrying capacity. The carrying capacity of the watershed becomes the basis for consideration in the watershed management plan. The purpose of this research is to study the biophysical carrying capacity of the upstream Ciujung Sub-basin. Biophysical aspects of watershed include percentage of degraded land, percentage of vegetation, erosion index, runoff regime coefficient, annual runoff coefficient, sedimentation, flood events, and water use index. It was scored based on Indonesia Forestry Minister Regulation No. P.61/Menhut-II/2014. The result showed that degraded land percentage, erosion index, yearly runoff coefficient, sedimentation, and flood event were severe, vegetation belongs to the very bad category, and water use index were in a medium stage. The carrying capacity in Ciujung Hulu Watershed was in poor condition with a score total of 140,5.